2020
DOI: 10.4028/www.scientific.net/msf.1005.166
|View full text |Cite
|
Sign up to set email alerts
|

Application of Taguchi Methodology in Evaluating the Rockwell Hardness of SLA 3D Printed Polymers

Abstract: Stereolithography (SLA) is an Additive Manufacturing technology which converts liquid resins to solid parts layer-by-layer by selectively curing the liquid resin using a (laser) light source. The mechanical properties SLA 3D printed parts are not yet determined or estimated before printing. Thus, this study aims to identify the optimum 3D printing configuration based on the indentation hardness properties of SLA-printed polymer parts. Taguchi approach was used in identifying the optimum 3D printing configurati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…These tests have been very beneficial for material evaluation and ensuring quality control. [ 90 ] The earlier mechanical tests discussed in this paper are quasi-static tests because they are conducted at a low strain rate. However, since many materials fail suddenly under the high strain rate condition, material behavior must be investigated using the impact test method when subjected to impact loading.…”
Section: Methods Of Metrologymentioning
confidence: 99%
“…These tests have been very beneficial for material evaluation and ensuring quality control. [ 90 ] The earlier mechanical tests discussed in this paper are quasi-static tests because they are conducted at a low strain rate. However, since many materials fail suddenly under the high strain rate condition, material behavior must be investigated using the impact test method when subjected to impact loading.…”
Section: Methods Of Metrologymentioning
confidence: 99%
“…It offers excellent electrical, thermal, and mechanical properties. Graphene is also known to contain antimicrobial effects [9][10][11][12][13][14][15]. The work concluded that the 3D printed nanocomposite made of a mixture of PLA, TPU, and GO showed excellent properties, thermally and mechanically, as well as cell viability, which allowed the nanocomposite to be used in various fields and as a good potential in tissue engineering fields [15,18,158,159].…”
Section: Biocompatibility Of 3d Printing Materialsmentioning
confidence: 96%
“…It also minimizes the number of parts and reduces the total weight by altering parameters such as the infill density and infill pattern. In recent years, this technology has been used in various applications in electronics, water filtration, robotic systems, art, architecture, optics, biology, nanotechnology, aerospace, civil engineering, and tissue engineering [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, 3D scanning technology will be applied to scan and measure the deviation of dimensions for samples. Then, the Taguchi method will be designed, and the process results of the research will be tested [13]. When the parameters set in the proposed study are used for the predictive deviation of products, the results can be used for part design and manufacturing process by 3D printing technology that method becomes more accurate and efficient.…”
Section: Introductionmentioning
confidence: 99%